Phage-Mediated Explosive Cell Lysis Induces the Formation of a Different Type of O-IMV in Shewanella vesiculosa M7T - Baeza, Nicolás; Delgado, Lidia; Comas, Jaume; Mercade, Elena (Frontiers in Microbiology, 2021)
Shewanella vesiculosa M7T is a cold-adapted Antarctic bacterium that has a great capacity to secrete membrane vesicles (MVs), making it a potentially excellent model for studying the vesiculation process. Shewanella vesiculosa M7T undergoes a blebbing mechanism to produce different types of MVs, including outer membrane vesicles (OMVs) and outer-inner membrane vesicles (O-IMVs). More recently, other mechanisms have been considered that could lead to the formation of O-IMVs derived from prophage-mediated explosive cell lysis in other bacteria, but it is not clear if they are of the same type. The bacterial growth phase could also have a great impact on the type of MVs, although there are few studies on the subject. In this study, we used high-resolution flow cytometry, transmission electron microscopy (TEM), and cryo-electron microscopy (Cryo-EM) analysis to determine the amount and types of MVs S. vesiculosa M7T secreted during different growth phases. We show that MV secretion increases during the transition from the late exponential to the stationary phase. Moreover, prophage-mediated explosive cell lysis is activated in S. vesiculosa M7T, increasing the heterogeneity of both single- and double-layer MVs. The sequenced DNA fragments from the MVs covered the entire genome, confirming this explosive cell lysis mechanism. A different structure and biogenesis mechanisms for the explosive cell lysis-derived double-layered MVs was observed, and we propose to name them explosive O-IMVs (EOIMVs), distinguishing them from the blebbing O-IMVs; their separation is a first step to elucidate their different functions. In our study, we used for the first time sorting by flow cytometry and Cryo-EM analyses to isolate bacterial MVs based on their nucleic acid content. Further improvements and implementation of bacterial MV separation techniques is essential to develop more in-depth knowledge of MVs.